2017
DOI: 10.1038/s41467-017-00969-8
|View full text |Cite
|
Sign up to set email alerts
|

Single nucleus sequencing reveals spermatid chromosome fragmentation as a possible cause of maize haploid induction

Abstract: Production of maternal haploids using a conspecific haploid inducer is routine and highly efficient in maize. However, the underlying mechanism of haploid induction (HI) is unclear. We develop a method to isolate three nuclei from a pollen grain and four microspores from a tetrad for whole-genome sequencing. A high rate of aneuploidy is observed at the three-nucleus stage (6/22 pollens) rather than at the tetrad stage (1/72 microspores) in one HI line CAU5. Frequent aneuploidy is also observed in another two i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
63
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(64 citation statements)
references
References 41 publications
1
63
0
Order By: Relevance
“…Moreover, [14] multiplex editing of three (REC8, PAIR1 and OSD1) key meiotic genes in hybrid rice leads to the production of clonal diploid gametes and tetraploid seeds. Next, editing of the MTL [4,59] gene involved in fertilization results in the induction of haploid seeds in hybrid rice. By simultaneous editing of these four endogenous genes in hybrid rice using the CRISPR/Cas9 system, plants able to propagate clonally through seeds were obtained.…”
Section: Synthetic Apomixis Through Genome Editing To Preserve Hybridmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, [14] multiplex editing of three (REC8, PAIR1 and OSD1) key meiotic genes in hybrid rice leads to the production of clonal diploid gametes and tetraploid seeds. Next, editing of the MTL [4,59] gene involved in fertilization results in the induction of haploid seeds in hybrid rice. By simultaneous editing of these four endogenous genes in hybrid rice using the CRISPR/Cas9 system, plants able to propagate clonally through seeds were obtained.…”
Section: Synthetic Apomixis Through Genome Editing To Preserve Hybridmentioning
confidence: 99%
“…Wang et al, [14], reported the MiMe does not significantly reduced the seed production whereas, the mutation in MTL leads toward haploid induction at expense of seed production in rice. Similarly, in Maize the large scale chromosome fragmentation caused reduction in fertility owing to post-meiosis in the mtl gametophyte [4]. The fragmentation leads toward the imbalance between genome of both maternal and paternal side.…”
Section: Limitations To Synthetic Apomixismentioning
confidence: 99%
See 1 more Smart Citation
“…First, we showed that multiplex editing of three key meiotic genes 5,6 in hybrid rice leads to the production of clonal diploid gametes and tetraploid seeds. Next, editing of the MATRILINEAL ( MTL ) gene that involved in fertilization 7,8 results in the induction of haploid seeds in hybrid rice. By simultaneous editing of these four endogenous genes in hybrid rice using the CRISPR/Cas9 system, we obtained in one generation plants able to propagate clonally through seeds.…”
mentioning
confidence: 99%
“…This ploidy doubling must be prevented to achieve apoximis. Recently, it was reported that the MATRILINEAL ( MTL ) gene, a sperm-specific phospholipase, triggers haploid induction in maize 7,8 . To test whether the homologous gene could be manipulated to induce haploid in self-fertilized hybrid rice, we edited the MTL gene in CY84 (Fig.…”
mentioning
confidence: 99%